Tahfidz Learning Management at Pesantren-based Higher Education - Murniyanto, Murniyanto; Siswanto, Siswanto (JURNAL AL-TANZIM, 2022)
This research is motivated by the condition of new students who enter Ma'had Al-Jami'ah IAIN Curup who have different educational backgrounds in understanding the Qur'an. This study aimed to understand the management of Tahfidz Qur'an learning at IAIN Curup. This research is a qualitative research type of case study. Observation, interviews, and documentation carried out data collection techniques. The subjects of this research are administrators, ustadz and ustazah, and students. Then the data analysis starts with data reduction, presentation, and conclusion drawing. The results showed that; Tahfidz Al-Qur'an learning management at IAIN Curup includes three stages, namely, planning, which consists of praying and memorizing muraja'ah; implementation consisting of recitation techniques, and understanding the meaning, memorization techniques, and deposit techniques and the evaluation stage in the form of an oral test. Furthermore, the application of the method used at Ma'had Al-Jami'ah IAIN Curup is unique, namely the technique of understanding meaning.